Evolving treatment approaches for the management of metastatic castration-resistant prostate cancer – role of radium-223 - Mukherji D; El Dika I; Temraz S; Haidar M; Shamseddine A (Dove Medical Press, 2014)
Deborah Mukherji,1 Imane El Dika,1 Sally Temraz,1 Mohammed Haidar,2 Ali Shamseddine11Department of Hematology/Oncology, 2Department of Nuclear Medicine, American University of Beirut Medical Center, Beirut, LebanonAbstract: Radium-223 is a first-in-class alpha particle-emitting radiopharmaceutical approved for the treatment of bone metastatic castration-resistant prostate cancer. Radium-223 is administered intravenously with no requirement for complex shielding and specifically targets areas of bone metastasis. In a randomized placebo-controlled Phase III study, treatment with radium-223 was shown to improve overall survival, time to skeletal-related events, and health-related quality of life. Apart from radium-223, the cytotoxic chemotherapy agents docetaxel and cabazitaxel, androgen biosynthesis inhibitor abiraterone acetate, novel anti-androgen enzalutamide, and immunotherapy sipuleucel-T have also been shown to improve survival of men with advanced prostate cancer in Phase III trials. This review will outline current treatment approaches for advanced prostate cancer with a focus on the role of radium-223 in changing treatment paradigms.Keywords: Alpharadin, alpha-emitting radionuclide, bone metastasis